Erectile function in prostate cancer-free patients who underwent prostate saturation biopsy - ŞİMŞEK, FERRUH (ELSEVIER SCIENCE BV, 2008)
Objective: To evaluate the erectile function following transrectal ultrasound-guided saturation biopsies of the Prostate. Materials and methods: Of the 150 patients included in the study, those with persistently elevated prostate-specific antigen (PSA) level underwent saturation biopsy. A median of 22-core (minimum: 20; maximum: 30) prostate saturation biopsies was taken. Patients were evaluated for erectile function prebiopsy with the 5-item version of the International Index of Erectile Function (IIEF-5) and the IIEF-Erectile Function (IIEF-EF) domain scoring. Concomitant systemic diseases and medications that would interfere with erectile function were recorded. Eighty-eight patients reported to be prostate cancer-free underwent further evaluation with the IIEF-5 questionnaire at 1 and 6 mo postbiopsy. Severity of erectile dysfunction (ED) was classified into four categories. Results: The patients' ages, serum PSA levels, prostate volumes, and number of cores showed no significant correlation with changes in ED scores after the prostate saturation biopsies. According to the IIEF-5, for patients who were previously potent and found to be free of prostate cancer, the ED rates were 11.6% at the first month, and no ED was reported at the sixth month of evaluation. IIEF-5 and IIEF-EF domain scores displayed a statistically significant difference between baseline and first-month scores, but not between baseline and sixth-month scores, which returned to baseline values. Conclusions: Although saturation biopsy of the prostate is a safe procedure on the basis of erectile function, the minimal risk of temporary postbiopsy ED should be discussed with previously potent patients. (C) 2007 European Association of Urology. Published by Elsevier B.V. All rights reserved.
Keywords: anxiety; erectile dysfunction; prostate; prostate cancer; saturation biopsy; INTERNATIONAL-INDEX; DYSFUNCTION; ANXIETY; IMPACT; PAIN